Lasita, Riley County - VanGilder, Jeremiah T. (Kansas State University, The Chapman Center for Rural Studies, 2011)
This study will focus on Lasita, Fancy Creek Township, Riley County, Kansas. Lasita is an example of a typical turn of the 20th century rural town where the railroad influenced the establishment and prosperity of the town, and the automobile and Great Depression influenced the demise. This study uses plat maps, photographs, biographies, memoirs, and records.
Jeremiah T. VanGilder, “Lasita, Riley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/44.
Keywords: Charles Sebring; Fancy Creek; Kansas Central Railroad; Lasita; Leonardville; Riley County